DOI: 10.11606/t.12.2017.tde-21062017-113719
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure e influência social na captação de recursos em organizações sem fins lucrativos

Abstract: Em primeiro lugar, agradeço a Deus o dom da vida e me permitir chegar até aqui, dando-me toda a capacitação e inspiração para concluir esta tese. Agradeço a todos que oraram por mim, mesmo sem meu conhecimento, pois em momentos difíceis as orações foram primordiais para que eu me mantivesse na caminhada. Minha sincera gratidão também ao meu esposo Rodney Dohopiati Chuver, a quem eu amo e que me apoiou em tudo, suportando-me em momentos árduos com palavras sábias que me propiciaram conselhos sábios que muito co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
5

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 81 publications
1
3
0
5
Order By: Relevance
“…Other studies [11,20,21,24) identified positive relationships between the audit committee, information symmetry and decision optimization. In agreement, the study by Azevedo [9], Valência, Queiruga, and González-Benito [15], Hasnan et al [16], Charles and Kim [17], Yeo, Chong, and Carter [18], Hommerová and Severová [19] and Lacruz et al [22] found that the increase in donation levels resulted from corporate governance, internal controls and compliance practices.…”
Section: Adequacy Of Management Practices Regarding the Organizationa...supporting
confidence: 62%
See 3 more Smart Citations
“…Other studies [11,20,21,24) identified positive relationships between the audit committee, information symmetry and decision optimization. In agreement, the study by Azevedo [9], Valência, Queiruga, and González-Benito [15], Hasnan et al [16], Charles and Kim [17], Yeo, Chong, and Carter [18], Hommerová and Severová [19] and Lacruz et al [22] found that the increase in donation levels resulted from corporate governance, internal controls and compliance practices.…”
Section: Adequacy Of Management Practices Regarding the Organizationa...supporting
confidence: 62%
“…An example is the fact that the entities' financial reports are no longer an exception, but a rule. This demonstrates the con-cern existing with the quality of information for decision-making brought by studies such as those by Bromley and Powell [5], Haack and Schoeneborn [6], Ko and Liu [7] and, consequently, with the legitimacy and reputational value of these entities [8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Considerando a legibilidade da accountability como fator de compreensibilidade dos atores envolvidos no processo de captação, utilização e divulgação dos resultados da organização, inclusive os sociais (Jang & Rho, 2016;Hesarzadeh & Bazrafshan, 2018;Caldas & Freire, 2020 ), os fatores estruturais dos Conselhos e órgãos de controle dos municípios envolvidos (Uygur, 2020;Azevedo, 2017, Ayliffe et al, 2017 e a eficiência nos processos de doação para projetos sociais (Yao, 2015;Degasperi & Mainardes, 2017 ) e os processos de comunicação e controle social (Entschew & Suchanek, 2017).…”
Section: Referencia Teóricaunclassified